Food allergy and alternative-complementary medicine. - Rovatti, G. (European Journal of Pediatric Dermatology, 2003)
The difficulties sometimes encountered in establishing a correct and sound diagnosis of food hypersensitivity, together with the belief that many pathologic conditions may be caused by or associated with adverse reactions to food, have led many patients to have recourse to non-conventional diagnostic techniques. The aim of this paper is to describe the most common diagnostic techniques used in alternative and complementary medicine in dealing with food hypersensitivity. The available scientific data regarding each of these methods and their reliability are presented and discussed.